Predictors for early detection of severe Dengue with shock / Quah Chai Hoong - Quah, Chai Hoong (2019)
It is vital to detect severe dengue with severe plasma leakage in the early stage to avoid worsening shock. Traditional methods to detect shock in severe dengue are based on the clinical assessment of the physicians in charge. They depend on the presence of symptoms such as cold and sweaty skin, blood pressure, heart rate , and presence of bleeding to aid in disease identification for treatment, epidemiologic surveillance, and studies of dengue pathogenesis. This has delayed the management of severe dengue which substantially increases the likelihood of morbidity and mortality. This study is conducted to identify features that are more informative in relation with severe dengue with shock. Methods We studied the admissions to the General Intensive Care Unit at the University Malaya Medical Centre (UMMC), Kuala Lumpur, Malaysia in the past 1 year after obtaining approval from the Medical Ethical Committee UMMC. We included all patients who were diagnosed with dengue infection and aged 18 years old and above. Physiological data of patients who were diagnosed with dengue are collected from University Malaysia Medical Centre electronic medical records. We merged various clinical and biochemical parameters to build the prediction model for early detection of shock in dengue patients because any single clinical parameter does not have strong discriminative power. Therefore, major data mining methods are adopted to train the iv multi-parameters model. Type of data collected ranges from primary measures and secondary measures of vital signs to laboratory data that require longer time to process and obtain. Data were collected for this study are: A) Physiological parameters/Vital signs: Primary measures: Heart rate, respiratory rate (RR), oxygen saturation (SpO2), blood pressure (systolic, diastolic and mean blood pressure) B) Laboratory data: Full blood count (FBC): hemoglobin (Hb), hematocrit, platelet count, white blood cell count Liver function test (LFT): total protein, total bilirubin, aspartate aminotransferease (AST), Alanine aminotransferase (ALT), albumin, alkaline phosphatase, Arterial blood gas (ABG): oxygen saturation, pO2, pCO2, FiO2, bicarbonate, pH, base excess, Lactate Coagulation test: partial thromboplastin time (ATT), INR Renal function test (RFT): Urea, creatinine, sodium, potassium We classified the cases in this study based on the definition of disease severity in 2009 WHO guidelines. Cases will be characterized as non-severe dengue (non-SD) and severe dengue (SD). Shock is defined as systolic blood pressure < 90 mmHg or narrow pulse pressure < 20 mmHg. Results: Of the 155 patients, 7 patients had dengue shock syndrome compared to 148 patients did not experienced any shock symptoms. This study identifies platelet count is the only significant factor that was associated with subsequent development of severe dengue with shock. v For the baseline results, there were no differences in most of the variables being analysed. Only the platelet levels showed a significant difference between the shocked and nonshocked subjects (81.00 vs 16.00, p=0.015). There were no significant differences between the groups for age (p=0.408), BMI (p=0.183), haemoglobin (p=0.408), haematocrit (p=0.390), total white cells (p=0.461), INR (p=0.384) and APTT time (p=0.388), ALT (p=0.301), AST (p=0.274) and lactate levels (p=0.198). For the 2nd day analysis, it was only the platelet parameter again which showed a significant difference between the shocked and non-shocked subjects (61.00 vs 21.50, p=0.011). There were no significant differences between the groups for haemoglobin (p=0.389), haematocrit (p=0.454), total white cells (p=0.875), INR (p=0.559) and APTT time (p=0.470), ALT (p=0.715), AST (p=0.667) and lactate levels (p=0.314). Conclusions: Thrombocytopenia during acute febrile phase is an early predictor of severe dengue with shock. Patients with low platelets in acute febrile phase of dengue fever need more medical attention as there is a higher chance of progression to severe dengue with shock. But age, BMI, haematocrit, haemoglobin, platelet, WBC, INR, APTT, ALT, AST and lactate in acute febrile phase are unlikely to predict DHF.